2011
DOI: 10.3109/03639045.2011.575163
|View full text |Cite
|
Sign up to set email alerts
|

Development of multiple-unit colon-targeted drug delivery system by using alginate:in vitroandin vivoevaluation

Abstract: Drug delivery systems to the colon are being actively investigated. However, it is difficult to ensure that an oral preparation disintegrates specifically in the human colon. In this study, a pH- and enzyme-controlled, colon-targeted tablets (PECCTT) was established by using outer pH-coated layer and inner alginate-coated compression layer. The influence of the amount of alginate and enteric coat thickness on drug release had been investigated and the formulation that contained 30% alginate in compression laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…However, it should be born in mind that colonic enzymes or bacteria were not included in the simulated colonic media. Alginate has been reported to be fermented by human colonic microflora, whereas Lai et al reported that prednisolone release from alginate‐coated tablets in SCF containing 3 U/mL β‐mannanase was similar to that in 4% (w/v) rat cecal content solution. Therefore, the present finding of limited NP release from alginate microcapsules and aggregation of released NPs may not represent in vivo behavior.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, it should be born in mind that colonic enzymes or bacteria were not included in the simulated colonic media. Alginate has been reported to be fermented by human colonic microflora, whereas Lai et al reported that prednisolone release from alginate‐coated tablets in SCF containing 3 U/mL β‐mannanase was similar to that in 4% (w/v) rat cecal content solution. Therefore, the present finding of limited NP release from alginate microcapsules and aggregation of released NPs may not represent in vivo behavior.…”
Section: Resultssupporting
confidence: 90%
“…The maximum mean colonic transit time in humans is reported to be as high as 33 h in men and 47 h in women . Incubation time in SCF was confined to 6 h which is expected to coincide with transit to the sigmoid colon …”
Section: Methodsmentioning
confidence: 82%
“…Computed Tomography and X-rays• Imaging using radio-opaque substances is able to identify the position of formulations following oral administration.• Radio-opaque substances are typically needed for imaging with barium sulphate often used once incorporated into the dosage form [35–37], however limited detail of the surrounding soft tissue anatomy is provided.• High contrast resolution images come with a drawback of requiring greater doses of radiation [38]. This reduces the number of scans that can be performed on a single subject.• Dissolution of tablets was described by Vemula et al [36] however the detail was limited, and the time course of data acquisition was over several hours at set time intervals, until the tablet was no longer seen.• Lai and colleagues [28] performed a study where they used a combination of single-photon emission computed tomography/computed tomography (SPECT/CT) to visualise the movement of a colon targeting dosage forms from administration to site of release [28]. SPECT/CT was able to show disintegration of the tablet and the position in the GIT at which this was occurring [28].…”
Section: Introductionmentioning
confidence: 99%
“…This reduces the number of scans that can be performed on a single subject.• Dissolution of tablets was described by Vemula et al [36] however the detail was limited, and the time course of data acquisition was over several hours at set time intervals, until the tablet was no longer seen.• Lai and colleagues [28] performed a study where they used a combination of single-photon emission computed tomography/computed tomography (SPECT/CT) to visualise the movement of a colon targeting dosage forms from administration to site of release [28]. SPECT/CT was able to show disintegration of the tablet and the position in the GIT at which this was occurring [28]. Ultrasound• US uses relatively affordable and portable US machines, increasing accessibility, whilst providing real time acquisition [39].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Xing et al 183 assessed drug release from alginate MCs in the same buffer for 3 h and Thakral et al 155 tested Eudragit ® S100-coated chitosan microspheres for 6 h. To evaluate the susceptibility of microflora-activated systems to the in vivo colonic microflora environment, rat caecal content or colonic enzymes can be included in the simulated colonic fluid. With this model, a number of studies 6,158,[184][185][186] have shown the colon-targeting capacity of the carrier systems investigated, for the drug release from the carrier was significantly enhanced in the presence of rat caecal content or colonic enzymes. Although the in vitro release model cannot represent the full factors of in vivo conditions, it is still a useful tool for formulation development by comparing the response of different formulations to mimic biological factors (e.g.…”
Section: In Vitro Evaluation Of Colon-specific Delivery Systemsmentioning
confidence: 99%